PREPARATION OF CHOCOLATE COATED DATE FRUIT STUFFED WITH DATE FRUIT POWDER,ALMONDS AND CHIA SEEDS AND ITS ANALYSIS (International Journal of Food and Nutritional Sciences, 2023)
The development and analysis of chocolate-coated date fruit were investigated in this research paper. Proximate analysis was conducted to determine the nutritional composition, including moisture, protein, fat, carbohydrates, and ash content. Sensory analysis was performed to evaluate the organoleptic properties such as taste, texture, aroma, and overall acceptability of the chocolate-coated date fruit. Furthermore, the antioxidant activity of the product was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The shelf life analysis was conducted using the Agar Diffusion Method to determine the product's microbial stability over time. The results of the proximate analysis showed that the chocolate-coated date fruit had favorable nutritional composition